Left ventricular strain patterns and their relationships with cardiac biomarkers in hypertrophic cardiomyopathy patients with preserved left ventricular ejection fraction - Zhang, Lisha; Wan, Yixuan; He, Bo; Wang, Lei; Zhu, Dongyong; Gao, Fabao (Frontiers in Cardiovascular Medicine, 2022)
Aims This study aims to assess left ventricular (LV) function in hypertrophic cardiomyopathy (HCM) patients with preserved left ventricular ejection fraction (LVEF) by LV strain patterns based on cardiac magnetic resonance feature tracking (CMR-FT) and to explore the relationships between LV strain patterns and cardiac biomarkers in these patients, such as cardiac troponin (cTnT) and N-terminal prohormone of the brain natriuretic peptide (NT-proBNP). Methods A total of 64 HCM patients with preserved LVEF and 33 healthy people were included in this study. All subjects underwent contrast-enhanced CMR, and all patients took blood tests for cTnT and NT-proBNP during hospitalization. Results Despite the absence of a significant difference in LVEF between HCM patients and healthy controls, almost all global and segmental strains in radial, circumferential, and longitudinal directions in the HCM group deteriorated significantly as compared to controls (p < 0.05). Moreover, some global and segmental strains correlated significantly with NT-proBNP and cTnT in HCM patients, and the best correlations were global radial strain (GRS) (r = −0.553, p < 0.001) and mid-ventricular radial strain (MRS) (r = −0.582, p < 0.001), respectively, with a moderate correlation. The receiver operating characteristic (ROC) results showed that among the LV deformation parameters, GRS [area under the curve (AUC), 0.76; sensitivity, 0.49; specificity, 1.00], MRS (AUC, 0.81; sensitivity, 0.77; specificity, 0.79) demonstrated greater diagnostic accuracy to predict elevated NT-proBNP, and abnormal cTnT, respectively. Their cut-off values were 21.17 and 20.94%, respectively. Finally, all global strains demonstrated moderate, good, and excellent intra- and inter-observer reproducibility. Conclusion LV strain patterns can be used to assess the subclinical cardiac function of HCM patients on the merit of being more sensitive than LVEF. In addition, LV strain patterns can detect serious HCM patients and may be helpful to non-invasively predict elevated NT-proBNP and cTnT.